MONITORING AND REMOVAL OF METALS FROM ACID MINE DRAINAGE THROUGH AN ANAEROBIC REACTOR - Yabuki, Lauren N. M. [UNESP]; Nogueira, Elis Watanabe; Damianovic, Márcia H. R. Z.; Menegário, Amauri A. [UNESP]; Garcia, Marcelo L. [UNESP] (Universidade Estadual Paulista - Campus de Tupa, 2020)
An efficient way to treat effluents from acid mine drainage (AMD), compared to conventional acid neutralization treatments, is through the application of anaerobic biological processes that use sulfate reducing bacteria (BRS) presenting sulfate removal, alkalinization of the medium and metal precipitation. An efficient way to treat this type of effluent, compared to conventional acidification-neutralization process, is by applying anaerobic biological processes that use sulphate-reducing bacteria (SRB) presenting sulphate removal, medium alkalinization and metal precipitation. The present study aimed to monitor the total concentration of Co, Cu, Fe, Mn, Mo, Ni, Se, V, W and Zn and to evaluate their metal removal efficiencies in a Down-Flow Fixed-structured Bed Reactor (DFSBR), used to treat effluents from sulfate-rich synthetic AMD. The anaerobic process for the AMD treatment has obtained a high performance with average removal efficiencies, from Phases II to IV of 92 ± 4, 87 ± 8, 71 ± 21, 61 ± 24, 92 ± 4 e 86 ± 8 for Co, Cu, Fe, Mn, Ni and Zn, respectively. The anaerobic treatment of AMD by the DFSBR reactor proves to be a promising alternative for the metal removal besides sulfate reduction and pH elevation, according to the conditions described in this study, and a promising and complementary option for the Mn removal, considered problematic as generally is not efficiently removed in real MADs, using conventional physicochemical processes.
MONITORAMENTO E REMOÇÃO DE METAIS EM UM REATOR ANAERÓBIO APLICADO AO TRATAMENTO DE DRENAGEM ÁCIDA DE MINA
Keywords: Acid mine drainage (AMD); Biologic treatment; Metal removal